METHODOLOGICAL AND APPLICATIVE ASPECTS OF ACCOUNTING FOR CIVIL PARTNERSHIP CONTRACTS IN THE CONTEXT OF PUBLIC-PRIVATE PARTNERSHIPS - Angela POPOVICI; Corina PANUS (Economica)
Public-Private Partnerships (PPP) are widely used in the Republic of Moldova to mobilize resources and expertise for the development of infrastructure and public services, given the constraints of limited public funds. This study highlights the methodological and applicative challenges encountered in accounting for civil partnership contracts within the context of PPPs in Moldova. These challenges include: recognition and measurement of revenues and expenses, management of financial and operational risks, consolidation of accounts, and fiscal implications. The authors examine the distinctive characteristics of civil partnership contracts employed in PPPs and their impact on accounting practices, in line with the Methodological Guidelines on Accounting Particularities in Public-Private Partnerships (Methodological Guidelines) and the application of International Financial Reporting Standards (IFRS). The study provides an analysis of the accounting challenges specific to civil partnership contracts in Moldovan PPPs, addressing key issues such as revenue, expenses, risks, and tax considerations.